The Challenges and the Opportunities of introducing Organic KitKat Chocolate by Nestle (A Study Case: NESTLE) - Sherleen Vernice Djarum; Daisy Mui Hung Kee; Nurul Nabilah Binti Azmin; Ramado Dipradelana Isdianto; Abdurrahman Omar Elghoul; Shantanu Somnath Pandit (Journal of The Community Development in Asia, 2019)
The issue that we are going to discuss in this report is the accusations that the company is facing regarding the violation of the Ethical marketing codes and manipulating customers with harmful ingredients inside its products. Also, we will introduce a new organic kitkat chocolate in the market and we will analysis the all strategies risks and opportunity of introducing this chocolate in the international market.